Báo cáo Giải trình, tiếp thu ý kiến đại biểu Quốc hội về việc tổ chức chất vấn tại Kỳ họp thứ 7 - Uỷ ban Thường vụ Quốc hội (2024)
Toàn văn Báo cáo Giải trình, tiếp thu ý kiến đại biểu Quốc hội về việc tổ chức chất vấn tại Kỳ họp thứ 7.